2012
DOI: 10.1093/cid/cis1006
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Nosocomial Bloodstream Infections: Antibiotic-Resistant Bacteria Increase the Total Burden of Infection

Abstract: Increased nosocomial BSI rates due to ARB occur in addition to infections caused by ASB, increasing the total burden of disease. Hospitals with high ARB infection rates in 2005 had an excess burden of BSI of 20.6 per 100 000 patient-days in a 10-year period, mainly caused by infections with ARB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
100
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 16 publications
(16 reference statements)
4
100
2
4
Order By: Relevance
“…P. aeruginosa is the cause of a high percentage of nosocomial infections in critically ill patients. In the EPIC Ⅱ study Pseudomonas species caused 19.9% of infections in the ICU [1] while another multicenter study concerning bloodstream infections coming from 9 countries, showed that P. aeruginosa was the cause of bacteremia in 5.3% of cases [23] . Several mechanisms are implicated in the development of resistance in P. aeruginosa strains.…”
Section: P Aeruginosamentioning
confidence: 99%
“…P. aeruginosa is the cause of a high percentage of nosocomial infections in critically ill patients. In the EPIC Ⅱ study Pseudomonas species caused 19.9% of infections in the ICU [1] while another multicenter study concerning bloodstream infections coming from 9 countries, showed that P. aeruginosa was the cause of bacteremia in 5.3% of cases [23] . Several mechanisms are implicated in the development of resistance in P. aeruginosa strains.…”
Section: P Aeruginosamentioning
confidence: 99%
“…stream infections, and they can have a mortality rate of 40 to 60% (3)(4)(5). Although bacteria are the predominant microorganisms, Candida species have emerged as one of the leading causes of hospital-acquired infections and are responsible for 80% of all nosocomial infections caused by fungi (6).…”
mentioning
confidence: 99%
“…S. aureus has a particular propensity for developing multidrug resistance (e.g., methicillin-resistant S. aureus [MRSA] and vancomycin-intermediate S. aureus [VISA]), and serious infections with such strains result in enhanced attributable mortality (3).…”
mentioning
confidence: 99%